A Command for Estimating Spatial-Autoregressive Models with Spatial-Autoregressive Disturbances and Additional Endogenous Variables. (July 2013) - Drukker, David M.; Prucha, Ingmar R.; Raciborski, Rafal
We describe thespivreg command, which estimates the parameters of linear cross-sectional spatial-autoregressive models with spatial-autoregressive disturbances, where the model may also contain additional endogenous variables as well as exogenous variables.spivreg uses results and the literature cited in Kelejian and Prucha (1998, Journal of Real Estate Finance and Economics 17: 99–121; 1999, International Economic Review 40: 509–533; 2004, Journal of Econometrics 118: 27–50; 2010, Journal of Econometrics 157: 53–67); Arraiz et al. (2010, Journal of Regional Science 50: 592–614); and Drukker, Egger, and Prucha (2013, Econometric Reviews 32: 686–733).